Reevaluating 30 cmH2O endotracheal tube cuff pressure: risks of airway mucosal damage during prolonged mechanical ventilation - Mu, Guo; Wang, Feixiang; Li, Qiang; Yu, Xuan; Lu, Bin (Frontiers in Medicine, 2024)
Background The optimal endotracheal tube (ETT) cuff pressure remains contentious. In the traditional consideration that the level 30 cmH2O is considered safe, balancing the prevention of reflux aspiration against airway mucosal damage. Whether this pressure level can cause potential damage to the airway mucosa remains to be discussed. Methods Airway mucosa damage and structural changes at 30 cmH2O were examined in patients under general anesthesia and in rabbit mechanical ventilation models. Prior to this, we also interviewed some anesthesiologists about the level of concern about ETT cuff pressure. Results A total of 634 valid questionnaires suggested that anesthesiologists generally do not pay enough attention to ETT cuff pressure and the average established cuff pressure significantly exceeded 30 cmH2O. Airway mucosa images of 100 general anesthesia patients with different ventilation duration indicated that maintaining the pressure at 30 cmH2O did not cause significant damage to airway mucosa in a short period of time, while it still caused damage to airway mucosa in patients with long-term ventilation, with damage severity increasing with longer ventilation periods. This correlated strongly with postoperative sore throat (R2 = 0.3884, p < 0.001). In rabbits, 4 h of ventilation at this pressure resulted in significant loss of ciliated epithelium and inflammation. Calculations suggested an effective dose (ED50) to prevent mucosal injury at a cuff pressure of 25.64 cmH2O (95% CI: 19.268–29.367 cmH2O). Conclusion The currently established cuff pressure of 30 cmH2O is associated with airway mucosal damage in both clinical and animal models. Lowering the safety threshold of cuff pressure may be necessary to mitigate mucosal injury.